Energetic efficiency of osmotic water transport across a root - Kargol, A; Markowski, A (Springer Heidelberg, 1996)
We consider an energetic efficiency eta(od) of the osmotic transport of water along a radial route in a root (from the soil to the root xylem) and of the vertical transport of water in xylem resulting from the osmotically generated root pressure. We model the root as a 1-membrane osmotic system. Knowing the transport parameters of the membrane we study the energetic efficiency as a function of the concentration C-m of a solution in the soil, the exudate concentration C-r and the height h of the water (exudate) transport in xylem. We conclude that the efficiency depends on all of the above quantities (C-m, C-r, h) There are, however, certain pairs of C-m and h (and C-r and h) for which the efficiency eta(od) is constant. It may point to a certain independence of a plant from the environmental factors.
Keywords: plant; root; osmosis; diffusion; energy